Analisis Budaya Organisasi, Komunikasi Dan Kinerja Organisasi Pada Dinas Pemuda Dan Olahraga Provinsi Bengkulu - Kimas Tando Agung; Willy - Abdillah; Trisna - Murni (Student Journal of Business and Management, 2021)
The study aim to examine was to describe and analyze organizational culture, communication and organizational performance at the Bengkulu Province Youth and Sports Office. The sample in this study were 75 employees at the Youth and Sports Office of Bengkulu Province. Data collection using questionnaires and interviews. Data analysis used quantitative and qualitative analysis. The results of the study prove that the organizational culture at the Dinas Pemuda dan Olahraga Province, the dimensions of innovation and risk taking get an average rating on good criteria with a value of 3.69. Organizational culture dimensions of 3.89 in good criteria. The dimension of outcome orientation is 3.84 (Good). Organizational culture has a dimension of orientation with a value of 3.88 (Good). The organizational culture has a team orientation dimension of 4.08 (Good). Organizational culture dimensions of aggressiveness with an average value of 3.88 (Good). The organizational culture a dimension of stability with an average value of 3.98 (Good). Communication of employees at the Dinas Pemuda dan Olahraga  Bengkulu Province is already good, this can be seen from the average score of 3.90. The results showed that the employee's response to communication the dimension of clarity (Clarity) had gone well with an average value of 3.94. Communication  the dimension of accuracy has been going well with an average value of 3.79. Communication context dimension has gone well with an average value of 3.75. Communication flow dimension has been going well with an average value of 3.91. The cultural dimension of communication is 3.20 (Good Enough). The organizational performance at the Dinas Pemuda dan Olahraga  Bengkulu Province obtained an average score of 3.96 (Good). The organizational performance of the Dinas Pemuda dan Olahraga  Bengkulu Province in the dimension of the percentage of youth who participate and play an active role in development with an average score of 3.93 (Good). The organizational performance dimension of the percentage of gifted sportsmen education with an average score of 3.93 (Good). The organizational performance  dimension of the number of outstanding athletes (national level is 4.10 (Good).Keywords: Organizational Culture, Communication, Organizational Performance